2007
DOI: 10.1002/ptr.2169
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of flaxseed oil against radiation‐induced hepatotoxicity in mice

Abstract: Flaxseed (linseed, Linum usitatissimum, Linaceae) is widely used for its edible oil in many parts of the world. The present study investigates the radioprotective and antioxidative potential of flaxseed oil (FO). Swiss albino mice were administered FO orally once daily for 15 consecutive days, then exposed to a single dose of 5 Gy of gamma radiation. Lipid peroxide, reduced glutathione and total protein were estimated in the liver. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), acid and alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…ALT in radiation-induced hepatotoxicity in mice 23 . Further, studies have reported the positive effects of flaxseed oil, or flaxseed per se, on kidney functions.…”
Section: Discussionmentioning
confidence: 99%
“…ALT in radiation-induced hepatotoxicity in mice 23 . Further, studies have reported the positive effects of flaxseed oil, or flaxseed per se, on kidney functions.…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al [55] reported the antioxidant activity of omega-3FA, as it reversed the effect of lead toxicity on ROS, protein carbonyl content and MDA levels, which may be attributed due to its high content of omega-3FA. Further, the oil present as main constituents in omega-3FA has an important role in free radical scavenging and singlet oxygen quenching [56] . In humans, the decreased levels of DHA, an important constituent of omega-3FA were found to be associated with neurodegenerative diseases, such as Alzheimer's disease [57] , suggesting the beneficial role of DHA to brain health.…”
Section: Discussionmentioning
confidence: 99%
“…injection of 100 μl of 20 mg/kg lead acetate [14] for 5 days. Group III received 0.3 ml of flaxseed oil by gavage (orally) once daily for 5 days at a dose of 1,000 mg/kg [15], and the animals of group IV received 0.3 ml flaxseed oil by gavage once daily for 5 days at a dose of 1,000 mg/kg body weight. An hour after the treatment with flaxseed oil, group IV was intrapritoneally injected with 100 μl of 20 mg/kg lead acetate for 5 days.…”
Section: Experimental Protocolmentioning
confidence: 99%